ANALISIS NILAI TAMBAH CRUDE PALM OIL (CPO) PADA PT. PASANGKAYU ASTRA AGRO LESTARI DI SULAWESI BARAT - Ikawati, Aisyah; Kalaba, Yulianti; Asih, Dewi Nur (AGROTEKBIS, 2018)
The study aimed to determine the added value generated by the processing of palm oil into crude palm oil (CPO) at the Pasangkayu Astra Agro Lestari limited company. The research location was purposively selected considering that the company is one of the largest companies in West Sulawesi producing CPO. The study used respondents consisted of the company leader and its employees. Primary and secondary data were used. The value added of palm oil processing into CPO was calculated using the Hayami analysis. The results show that the added value generated by the Pasangkayu Astra Agro Lestari limited company was IDR 29,047,891,308 with the added value ratio of 60.89%, the profit rate of 95.75% and the revenue earned of IDR 6,416,957,304.